Konsep Matching dalam Tradisi Kumpul Keluarga Masyarakat di Nusa Tenggara Timur - Tallo, Richardus Engel; Pati, Stefanus Aldisusanto; Tito, Marianus; Hambur, Oktavianus; Lian, Yohanes Pemandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Family gathering activities in East Nusa Tenggara (NTT) are a social tradition involving the collection of funds, goods, or animals during significant events such as marriages or funerals. This practice serves as a form of solidarity and mutual assistance within the community. Although these gatherings can incur substantial costs, the financial implications differ from ordinary accounting concepts. This research aims to explore the concept of "matching" within the family gathering tradition practiced by the people of East Nusa Tenggara. The methodology used for this research is qualitative, specifically library research. Data was collected by reviewing relevant literature related to the issue at hand. The researcher will analyze this data and present findings concerning the concept of matching in the family gathering tradition. The results demonstrate that the concept of matching in the business world differs from its application in indigenous communities. While businesses are obligated to recognize costs incurred over a specific period in relation to their income, the social accounting practices within these communities do not require a comparable income. Instead, the emphasis is placed on kinship relationships and the value of mutual cooperation, adhering to the norms that exist within the society.